FUNGSI BALAI PENGKAJIAN TEKNOLOGI PERTANIAN (BPTP) RIAU DALAM PEMBINAAN USAHA TANI (Studi pada Petani Komoditas Tanaman Padi Sawah di Kabupaten Rokan Hulu) - Vicky Harahap; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The research aims to identify and analyze the implementation of the functions Institute for Agricultural Technology (BPTP) in Riau Farmers Business Development, as well as supporting and inhibiting factors. Formulation of research problems are: (1) How does the implementation of the functions Institute for Agricultural Technology (BPTP) in Riau Farm Development on Commodity Crops Rice Farmers in Rokan Hulu? (2) What are the factors inhibiting and supporting the implementation of the functions Institute for Agricultural Technology (BPTP) in the Development of Farming Lists?The method used is descriptive method with qualitative approach. The research location is in BPTP Riau, and for the purposes of completeness of the data then data collection is also done at Rice Farmers in Rokan Hulu. As respondents used research informants consisting of Riau BPTP Head, Research and Extension Field in the institution, as well as Chairman of Farmers Group. Types of data are primary and secondary data. The data collection technique Interviews, documentation and observation. Data obtained and analyzed by descriptive-qualitative.This study concluded that: Function Assessment Institute for Agricultural Technology (BPTP) in Riau Farming Guidance has been done effectively. This is due to the establishment of clear objectives, scope of duties and responsibilities in accordance with the working ability as well as availability of human resources, delegation of authority and a clear division of labor and in accordance with their duties and functions, and the existence of good coordination of the tasks and subordinates. The inhibiting factors encountered in implementing coaching Riau BPTP farm through program assessment, assembly and development of appropriate agricultural technologies specific for Farmers, among others, are: (a) coordination and synchronization program with local government is less than optimal; (b) the presence of extreme climate change (droughts and floods); (c) the majority of farmer groups are less dynamic in a group activity; and (d) There is still limited availability of human resources in the Ministry of Agriculture. While supporting factor for BPTP Riau in implementing farming guidance through program assessment, assembly and development of appropriate agricultural technologies specific for the Farmers, among others, are: (a) technology introduced to farmers easy to implement, and in additionthe information technology easy obtained, profitable and can be applied in a wide expanse; (b) Participation of the farmers are relatively well enough to collaborate in the success of the program is implemented and accepted technology introduced; and (c) There is support for local government in expanding the application of the technology at the farm level.Keywords: function, development, farming, agricultural technology